Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What is $$50^2\frac{{n\choose 50}}{{n\choose 49}}+49^2\frac{{n\choose 49}}{{n\choose 48}}...1^2\frac{{n\choose 1}}{{n\choose 0}}$$.

i.e. $$\sum_{k=1}^{50} \frac{k^2\binom n k}{\binom n {k-1}}= ?$$

$$\text{MY ATTEMPT}$$ When I plugged $n=50$ I got $22100$ as the series is wave like, with maximum at $25$ which is $25\times 26$. So I calculated it on a calculator and multiplied the summation till $25\times 26$ and got it. But I want to calculate the general formula for summation. The answer given is $425(3n-98)$. Thanks!

share|cite|improve this question
It's not clear where that first parenthesis is supposed to close, but do you want an alternating sum? – Thomas Andrews Feb 26 at 13:55
If you'd fix your question so that people can figure out what you are asking, people might be able to help. Help people help you. – Thomas Andrews Feb 26 at 14:03
up vote 5 down vote accepted

$$\require{cancel} \sum_{r=1}^{50}r^2\frac{\binom nr}{\binom n{r-1}}\color{lightgrey}{=\sum_{r=1}^{50}r^\bcancel2\frac{\frac{\cancel{n(n-1)\cdots (n-r)}(n-r+1)}{\bcancel{r}\cancel{(r-1)!}}}{\frac{\cancel{n(n-1)\cdots (n-r)}}{\cancel{(r-1)!}}}}=\sum_{r=1}^{50}r(n-r+1)\\ =\sum_{r=1}^{50}nr-r(r-1)=\sum_{r=1}^{50} n\binom r1-2\binom {r}2\\ =n\binom {51}2-2\binom {51}3\\ =\frac 1{52}\binom {52}3(3n-98)\\ =425(3n-98)\quad\blacksquare$$

Note that if $n=50$, this reduces to $\binom {52}3$ as can be seen from above. This can also be proven directly as follows:

$$\sum_{r=1}^n r(n-r+1)=\sum_{r=1}^n\sum_{j=r}^nr=\sum_{j=1}^n\sum_{r=1}^j \binom r1=\sum_{j=1}^n\binom {j+1}2=\binom {n+2}3=\binom {52}3$$

share|cite|improve this answer

If the sum that you're interested in is: $$ \sum_{k=1}^{50}\frac{k^2\binom{n}{k}}{\binom{n}{k-1}}, $$ Then, $$ \sum_{k=1}^{50}\frac{k^2\binom{n}{k}}{\binom{n}{k-1}}=\sum_{k=1}^{50}\frac{k^2(n-k+1)}{k}=\sum_{k=1}^{50}k(n-k+1)=(n+1)\sum_{k=1}^{50}k-\sum_{k=1}^{50}k^2. $$ Then, using the formulas $$ \sum_{k=1}^{50}k=\frac{50\cdot 51}{2}=1275 $$ and $$ \sum_{k=1}^{50}k^2=\frac{50\cdot 51\cdot 101}{6}=42925, $$ you will get the negative of the answer at the end of the post (perhaps due to the negative confusion in the discussion above).

share|cite|improve this answer
which is $1275 n -41650 = 425(3n-98)$ and gives $22100$ when $n=50$. – Henry Feb 26 at 14:18

What to compute is not very clear. Anyway, if you want the value of: $$ 50^2\frac{\binom{n}{50}}{\binom{n}{49}}+49^2\frac{\binom{n}{49}}{\binom{n}{48}}+\ldots+1^2\frac{\binom{n}{1}}{\binom{n}{0}}=50(n-49)+49(n-48)+\ldots+1(n-0)$$ you just need to recall that $\sum_{k=1}^{m}k = \frac{m(m+1)}{2}$ and $\sum_{k=1}^m k^2 = \frac{m(m+1)(2m+1)}{6}$.

share|cite|improve this answer



share|cite|improve this answer
Okay but how to deal with $1.50+49.2+48.3+....+26.25)$ – Archis Welankar Feb 26 at 13:47
Can you check the location of the $n-p+1$ term from the $(n-(p-1))!$? – Michael Burr Feb 26 at 14:11
$\frac{\binom{n}{p}}{\binom{n}{p-1}}=\frac{\frac{n!}{p!(n-p)!}}{\frac{n!}{(p-1)!‌​(n-(p-1))!}}= \frac{(p-1)!(n-(p-1))!}{p!(n-p)!}= \frac{(p-1)!(n-p+1)!}{p!(n-p)!}= \frac{n-p+1}{p}$. – Michael Burr Feb 26 at 14:21
perhaps you meant $\frac {\frac np}{\frac n{p-1}}=\frac 1{p(n-p)}$... – hypergeometric Feb 26 at 14:38
I was referring to @Bacon's answer and trying to point that out. – hypergeometric Feb 26 at 14:45

Each term has the form

$$ k^2\frac{\binom{n}{k}}{\binom{n}{k-1}} $$

We can simplify this

$$ k^2\frac{\binom{n}{k}}{\binom{n}{k-1}} = \frac{k^2\frac{n!}{(n-k)!k!}}{\frac{n!}{(n-k+1)!(k-1)!}} = \frac{k^2*n!(n-k+1)!(k-1)!}{n!*k!(n-k)!} = \frac{k^2(n-k+1)}{k} = k(n-k+1) $$


$$ \begin{align} \sum_{k=1}^{\hat{K}} k^2\frac{\binom{n}{k}}{\binom{n}{k-1}} &=& \sum_{k=1}^{\hat{K}} k(n-k+1) \\&=& (n+1)\sum_{k=1}^{\hat{K}} k - \sum_{k=1}^{\hat{K}} k^2 \\&=& \frac{\hat{K}(n+1)(\hat{K}+1)}{2} - \frac{\hat{K}(\hat{K}+1)(2\hat{K}+1)}{6} \\&=& \frac{\hat{K}(3n - 2\hat{K} + 2)(\hat{K}+1)}{6} \end{align} $$

Now, in your specific case, $\hat{K} = 50$, so we get a sum of $425(3n-98)$ by plugging this into the above.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.